Convert to standard form
4x² + 25 = 20y
4x² - 20y + 25 = 20y - 20y
4x² - 20y + 25 = 0. . . .This is standard form
The middle term is - 20y
Find the sum of the middle term
Multiply the first term 4 by the last term 25 equals 100 and factor
Factors of 100 =
1 x 100
2 x 50
4 x 25
5 x 20
10 x 10. . .<=. .use these factors
- 10 and - 10 satisfy the sum of the middle term
insert - 10y and - 10y into the euation
4x² - 20y + 25 = 0
Group factor
4x² - 10y - 10y + 25
2y(2y - 5) - 5(2y -5)
(2y - 5)(2y - 5)
- - - - - - - -
roots
2y - 5 = 0
2y - 5 + 5 = 0 + 5
2y = 5
2y / 2 = 5 / 2
y = 5/2
- - - - - - - - - - - s-
2007-04-13 11:28:38
·
answer #1
·
answered by SAMUEL D 7
·
2⤊
0⤋
first subtract 20y from both sides to get 4y^2 - 20y + 25 = 0
knowing 25 is a perfect square makes life easy, because the only factor pairs are 25-1 and 5-5. And since you have -20y + 25, you know that both factors will subtract the whole #: (a-b)(c-d).
So you have either (2y-5)(2y-5) = 0 OR (y-5)(4y-5) = 0. FOIL them and see what you get. Failing that, use the quadratic formula.
2007-04-13 11:02:18
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
First: set the equation to equal "0" - subtract "20y" from both sides (when you move a term to the opposite side, always use the opposite sign).
4y^2 + 25 - 20y = 20y -20y
4y^2 + 25 - 20y = 0
*Make sure the expression is written in alpha descending order.
4y^2 - 20y + 25 = 0
Sec: factor... multiply the 1st & 3rd term to get 100. find two numbers that give you 100 when multiplied & -20 (2nd term) when added/subtracted. the numbers are (-10 & -10).
*Rewrite the expression with the new middle terms.
4y^2 - 10y - 10y + 25 = 0
*With 4 terms, group "like" terms & factor both sets of parenthesis.
(4y^2 - 10y) - (10y + 25) = 0
2y(2y - 5) - 5(2y - 5) = 0
(2y-5)(2y-5) = 0
(2y - 5)^2 = 0
Third: solve the "y" variable - eliminate the exponent by finding the square root of both sides.
V`(2y - 5)^2 = V`0
2y - 5 = 0
*Add 5 to both sides....
2y - 5 + 5 = 0 + 5
2y = 0 + 5
2y = 5
*ISolate "y" by dividing both sides by 2.
2y/2 = 5/2
y = 5/2
2007-04-13 11:08:52
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
1⤊
1⤋
4y^2-20y+25 =0
y=((20 +-sqrt(400-16*25))/8 = 20/8= 5/2 double root
4y^2-20y+25 = (2y-5)^2
2007-04-13 11:00:22
·
answer #4
·
answered by santmann2002 7
·
0⤊
0⤋
To solve this equation isolate everything on one side with zero on the other, so that you have
4y^2 - 20y + 25 = 0.
Now factor, or use the quadratic formula. In this case it factors into:
(2y-5)(2y-5)
or (2y-5)^2. This follows the identity that (ax-b)^2 = ax^2 - 2abx + b^2.
If you want the solution you'd solve 2y-5 = 0, or y = 5/2
2007-04-13 10:58:26
·
answer #5
·
answered by alphadelicious 5
·
0⤊
0⤋
4y^2+25=20y
4y^2 - 20y + 25 = 0
( 2y - 5) ( 2y - 5) = 0
y = 5/2
2007-04-13 10:58:00
·
answer #6
·
answered by John S 6
·
0⤊
0⤋
Rewrite the equation in standard form:
4y^2 - 20y + 25 = 0
Now you can plunk it into the quadratic formula and solve.
Alternatively, this one is fairly easy to solve by factoring
2007-04-13 10:56:51
·
answer #7
·
answered by dogsafire 7
·
0⤊
0⤋
You can write it as (2y-5)^2=0
so it must be that 2y-5=0
therefore, y=2 and 1/2
2007-04-13 10:57:14
·
answer #8
·
answered by Murat A 2
·
0⤊
0⤋
Firstly, you have to factorise it (do the working yourself)
Answer : (2y-5)(2y-5)=0. You MUST show your working.
Then find out the value for y
y=5/2
PS Do not copy me and hand this in as your homework. You are only cheating yourself.
2007-04-13 11:02:51
·
answer #9
·
answered by mr_maths_man 3
·
0⤊
0⤋
y^2-5y+25/4 = 0
(y-5/2)^2 = 0
y= 5/2
2007-04-13 10:57:47
·
answer #10
·
answered by Gaetano Lazzo 5
·
0⤊
0⤋